Amphiphilic BODIPY dye aggregates in polymeric micelles for wavelength-dependent photo-induced cancer therapy. Issue 31 (23rd April 2020) - Yan, Ziling; Wang, Mengya; Shi, Mengke; He, Yang; Zhang, Yi; Qiu, Shihong; Yang, Hong; Chen, Huabing; He, Hui; Guo, Zhengqing
Abstract : We have reported a facile strategy to tune the photoconversion of organic dye aggregates for achieving potent photo-induced cancer therapy. Abstract : Near-infrared (NIR) light-responsive nanoparticles of organic small-molecule dyes hold great promise as phototherapeutic dyes (PDs) for clinical translation due to their intrinsic merits, including well-defined structure, high purity, and good reproducibility. However, they have been explored with limited success in the development of photostable NIR PDs with extraordinary photoconversion for highly effective phototherapy. Herein, we have described amphiphilic BODIPY dye aggregates within the polymeric micelles (Micelles) as potent bifunctional PDs for dually cooperative phototherapy under NIR irradiation. Micelles possessed an intensive NIR absorption, high photostability, and favorable non-radiative transition, thereby exhibiting both remarkable singlet oxygen generation and photothermal effect under NIR light irradiation. Besides, Micelles had preferable cellular uptake, effective cytoplasmic drug translocation as well as enhanced tumor accumulation. Owing to the combined virtues, Micelles showed clinical potential as bifunctional PDs for photo-induced cancer therapy. This work thus provides a facile strategy to exploit advanced PDs for practical phototherapeutic applications.